Rome and China - Kim, Hyun Jin, 1982- author.
1 online resource
Keywords: "Rome and China provides an updated history and analysis of contacts and mutual influence between two of ancient Eurasia's most prominent imperial powers, Rome and China. It highlights the extraordinary interconnectivity of ancient Eurasia which allowed for actual contacts between Rome and China (however fleeting) and will examine in detail the influences from both ends of Eurasia which had cultural and political consequences for both Rome and China. This volume will be of interest to anyone working on the Roman Empire, Inner Asia, the Silk Routes and China in the classical and Late Antique periods"--